Infectious generosity : the ultimate idea worth spreading - Anderson, Chris, 1957 January 14- (Crown, 2024)
"From the bestselling author, media pioneer, and curator of TED, an inspiring book about one of humankind's defining but overlooked impulses, and how we can super-charge its potential to build a hopeful future. Recent years have been tough on optimists. Hopes that the Internet might bring people together have been crushed by the divisiveness of social media. But as head of TED, Chris Anderson has had a ringside view of the world's boldest thinkers sharing their most uplifting ideas. Inspired by them and the unique insights he gained from how online sharing transformed TED into a global beacon of transformative ideas, he believes there's a pathway back from outrage to optimism. It all comes down to reimagining the role that one of the most fundamental human virtues-generosity-can play in our connected era. What if generosity could become infectious generosity? Anderson shows how the same technologies that have bred negativity can also be mobilized as an exponential force for good, to create chain reactions of generous behavior. Every day, remarkable stories of individual acts of kindness have sparked remarkable ripple effects when shared online, achieving a level of impact never before possible. This book captures some of the most inspiring such stories, revealing their potential to solve problems and make people happier in the process. Gifts of time, talent, connection, and kindness have always been part of what it is to be a good human. But today they can be catalyzed to have world-changing, self-replicating impact. In Infectious Generosity, Anderson offers readers a playbook to fine-tune these actions, to take generosity from invisible to transformative. Infectious Generosity invites readers, as well as companies, investors, and organizations, to give more to the world than they take from it, and to wholeheartedly embrace new forms of infectious generosity. Doing so isn't merely a test of character-our entire future may depend on it. This book shows the way"--